Beliefs about education in prisons: Teachers' perceptions - Evangelina da Silva Sousa; Larissa Cavalcante Albuquerque; Ana Paula Moreno Pinho; Raimundo Eduardo Silveira Fontenele (Arizona State University, 2020)
The objective of this research was to analyze the beliefs normative, behavioral, and perceived control related to teaching in the prison environment, from the perspective of the Theory of Planned Behavior (Ajzen, 1991). It is exploratory, descriptive research, with a qualitative approach. Eight semi-structured interviews were carried out, with teaching agents working in the education of youth and adults and projects related to education in prison in the metropolitan region of Fortaleza - Ceará. The content of the interviews was analyzed through content analysis. The results indicated that the planned behavior of teaching in the prison environment of the interviewees is guided by three types of beliefs: behavioral, normative and perceived control. The results add information about teaching in the prison environment, contributing to the area of education, by providing an understanding of the role of teachers in an environment provided with stigma and prejudice; and management, since the prison units are public institutions that deal with social projects, whose dynamics are driven by contingencies intrinsic to this environment, by disciplinary power and by normalization. Also, the importance of the Theory of Planned Behavior is reinforced as an adequate theoretical model to predict human behavior.